2013
DOI: 10.1609/aaai.v27i1.8628
|View full text |Cite
|
Sign up to set email alerts
|

Vesselness Features and the Inverse Compositional AAM for Robust Face Recognition Using Thermal IR

Abstract: Over the course of the last decade, infrared (IR) and particularly thermal IR imaging based face recognition has emerged as a promising complement to conventional, visible spectrum based approaches which continue to struggle when applied in the real world. While inherently insensitive to visible spectrum illumination changes, IR images introduce specific challenges of their own, most notably sensitivity to factors which affect facial heat emission patterns, e.g. emotional state, ambient temperature, and alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Recall that the Hessian is informative regarding the nature of local appearance variation in an image [27]. In particular, considering the bacilli form elongated structures, we are interested in the loci which exhibit significant change in one principal direction (perpendicular to a bacterium) and little change in the other (along a bacterium), and these can be readily identified using the corresponding Hessian matrix eigenvalues [28]. More specifically, to create an enhanced image (in the context of our end goal), each pixel in the original image is replaced with the absolute value of the lower-magnitude value of the Hessian eigenvalue computed at the locus; see Figure 2.…”
Section: Image Processing-based Enhanced Representation Extractionmentioning
confidence: 99%
“…Recall that the Hessian is informative regarding the nature of local appearance variation in an image [27]. In particular, considering the bacilli form elongated structures, we are interested in the loci which exhibit significant change in one principal direction (perpendicular to a bacterium) and little change in the other (along a bacterium), and these can be readily identified using the corresponding Hessian matrix eigenvalues [28]. More specifically, to create an enhanced image (in the context of our end goal), each pixel in the original image is replaced with the absolute value of the lower-magnitude value of the Hessian eigenvalue computed at the locus; see Figure 2.…”
Section: Image Processing-based Enhanced Representation Extractionmentioning
confidence: 99%
“…Experimental results demonstrated that the LDDSCP descriptor, compared with other operators such as LBP and Gabor achieved prominent recognition accuracy and computational complexity. Ghiass et al [36,37] explored to describe the high-frequency detail in facial expressions and pose changes. They proposed a representation based on reliable anatomical features (such as vesselness features).…”
Section: Related Research Workmentioning
confidence: 99%
“…Ghiass et al. [36, 37] explored to describe the high‐frequency detail in facial expressions and pose changes. They proposed a representation based on reliable anatomical features (such as vesselness features).…”
Section: Related Research Workmentioning
confidence: 99%